Proceedings of the 2018 International Conference on Quantitative InfraRed Thermography 2018
DOI: 10.21611/qirt.2018.088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the heat generation process at vibrating contact defects

Abstract: Ultrasonic thermography is a promising technique for non-destructive evaluation of vibrating defects, due to its ability to perform fast, full field material inspections. A major drawback, however, is the inefficient conversion of vibrational energy to heat. To overcome this problem a solution based on Local Defect Resonance (LDR) excitation has been proposed. To validate this new concept and to find an optimal set of operational parameters it is crucial to have realistic models that can describe the ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The coupled thermal-electrical-mechanical analysis concludes that friction and viscoelastic losses are the heat sources of crack defects. Interestingly, this point was well supported by the work of Truyaert et al [34]. They simulated the propagation of ultrasonic shear waves in the aluminum specimen and the heat generation from the crack interface.…”
Section: Introductionmentioning
confidence: 54%
“…The coupled thermal-electrical-mechanical analysis concludes that friction and viscoelastic losses are the heat sources of crack defects. Interestingly, this point was well supported by the work of Truyaert et al [34]. They simulated the propagation of ultrasonic shear waves in the aluminum specimen and the heat generation from the crack interface.…”
Section: Introductionmentioning
confidence: 54%
“…They examined these mechanisms using experimental evidences, such as testing a samples including cracks and applying vibrations on the frequency range of 20–40 kHz. In 2018, Truyaert et al 24 studied generated heat in some samples using a numerical method. In this paper, it is shown that friction mechanism, will cause heat generation in different conditions of contact at the defect area.…”
Section: Introductionmentioning
confidence: 99%
“…The localized strain energy density around the defect and the resultant (normal and tangential) interaction of the defect's interfaces dissipate the vibrational energy as heat. Depending on the orientation, asperities and stress state of the defect, various heating mechanisms come into effect including: rubbing friction, adhesion hysteresis, viscoelastic damping, thermoelastic damping, and even plastic deformation at the crack tips [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%